Age‐related changes in afferent pathways and urothelial function in the male mouse bladder. (3rd January 2014) - Daly, Donna M.; Nocchi, Linda; Liaskos, Marina; McKay, Neil G.; Chapple, Christopher; Grundy, David
<x xml:space="preserve">Abstract</x> Key points The prevalence of bladder conditions such as overactive bladder syndrome and urinary incontinence significantly increases with age, but how bladder function is altered by ageing is unclear. Sensory nerves together with the epithelial lining of the bladder known as the urothelium play a key role in mediating bladder function. In aged male mice we find a significant increase in natural bladder voiding, augmented afferent nerve firing during bladder filling and a significant increase in urothelial responses to purinergic receptor stimulation. This suggests that with ageing there is increased purinergic transmission in the mouse bladder which may lead to increased sensation and result in bladder hypersensitivity. These findings help us better understand how the function of the bladder may be affected by advancing age. Abstract The prevalence of lower urinary tract storage disorders such as overactive bladder syndrome and urinary incontinence significantly increase with age. Previous studies have demonstrated age‐related changes in detrusor function and urothelial transmitter release but few studies have investigated how the urothelium and sensory pathways are affected. The aim of this study was to investigate the effect of ageing on urothelial‐afferent signalling in the mouse bladder. Three‐month‐old control and 24‐month‐old aged male mice were used. In vivo natural voiding behaviour, sensory nerve activity, urothelial cell function, muscle contractility, transmitter release and gene and protein expression were measured to identify how all three components of the bladder (neural, contractile and urothelial) are affected by ageing. In aged mice, increased voiding frequency and enhanced low threshold afferent nerve activity was observed, suggesting that ageing induces overactivity and hypersensitivity of the bladder. These changes were concurrent with altered ATP and acetylcholine bioavailability, measured as transmitter overflow into the lumen, increased purinergic receptor sensitivity and raised P2X3 receptor expression in the urothelium. Taken together, these data suggest that ageing results in aberrant urothelial function, increased afferent mechanosensitivity, increased smooth muscle contractility, and changes in gene and protein expression (including of P2X3). These data are consistent with the hypothesis that ageing evokes changes in purinergic signalling from the bladder, and further studies are now required to fully validate this idea.